Autoimmune thyroiditis and anti-thyroid antibodies in primary Sjögren's syndrome: a case–control study. Issue 5 (13th April 2004) - Tunc, R; Gonen, M S; Acbay, O; Hamuryudan, V; Yazici, H
Abstract : Objective: To determine the frequency of antithyroid antibodies and the presence of autoimmune thyroiditis among patients with primary Sjögren's syndrome. Design: A case–control study. Methods: 53 consecutive patients with primary Sjögren's syndrome, 30 with rheumatoid arthritis, 12 with secondary Sjögren's syndrome associated with rheumatoid arthritis, 17 with autoimmune thyroiditis, and 53 apparently healthy controls were studied for anti-TG and anti-TPO antibodies as well as serum thyroid hormones and TSH levels. Results: The overall frequencies of thyroid antibodies were 6/53 (11%) in primary Sjögren's syndrome, 2/30 (7%) in rheumatoid arthritis, 2/12 (17%) in secondary Sjögren's syndrome, 4/53 (8%) in healthy controls, and 16/17 (94%) in autoimmune thyroiditis. There was no difference in the frequency of the thyroid antibodies among the groups if patients with autoimmune thyroiditis were excluded (p = 0.415 for anti-TPO; p = 0.275 for anti-TG; p = 0.696 for either anti-TG and/or anti-TPO). Only two patients with primary Sjogren's syndrome had clinical hypothyroidism associated with autoimmune thyroiditis. Conclusions: In this Turkish population, no association between primary Sjögren's syndrome and autoimmune thyroiditis was found.